Methods for telepharmacy evaluation – A systematic review - Obradović, Dragisa; Ilkić, Jovana; Marinković, Valentina (Archives of Pharmacy, 2025)
The purpose of this systematic review was to analyze and summarize telepharmacy evaluation methods. A systematic review of articles was conducted in accordance with the PRISMA guidelines, using proper inclusion criteria. After the initial keyword search, duplicate check and screening for titles and abstracts, 22 papers entered the next phase, which was deep analysis. Most of the studies included in the in-depth analysis were classified as retrospective and were mainly focused on drug dispensing and pharmacotherapeutics monitoring and management. According to the Donabedian model, in 16 cases researchers analyzed processes, while 9 times the focus was set on the outcome. Using the ECHO model, it was found that 13 analyses were focused on clinical outcomes, 11 on humanistic, while economic outcome issues were explored in 2 papers. Risk of bias assessment showed that the highest risk of bias came from attrition bias. There are no unique recommendations on how telepharmacy evaluation should be performed. Interestingly, ECHO telepharmacy evaluation marginalized economic outcome issues, even though these outcomes are often a decision factor when it comes to the implementation. Our results confirm that stronger study designs and more rigorous evaluation methods are recognized as necessary so that new trends could be identified.
Keywords: telepharmacy; evaluation; pharmacy service; systematic review